Nodular colloid milium mimicking keloid. (9th March 2017) - Azimi, Seyyede Zeinab; Zargari, Omid; Rudolph, Robert I
Summary: Colloid milium is a rare cutaneous deposit disease that usually presents clinically by the development of yellowish translucent or flesh‐colored papules or plaques on sun‐exposed skin. Histologically, it is characterized by the presence of colloid in the dermal papillae. In this case report, we present a 52‐year‐old man who presented with a nodule on his upper lip that mistakenly was diagnosed and treated as keloid.